PENGARUH PENGETAHUAN, PROMOSI DAN LOKASI TERHADAP MINAT MASYARAKAT MENABUNG DI BANK SYARIAH INDONESIA KOTA JAMBI - Febby Hanum Khairunnisa; Habriyanto Habriyanto; Muhamad Subhan (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of knowledge, promotion, and location on people's interest in saving at Bank Syariah Indonesia in Jambi City.This study uses a quantitative method with a data collection technique through a questionnaire. The population in this study were people in Jambi City. The sample collection technique used the Slovin formula so that the number of samples in this study was 98.3 ≈ 100.The results of the study indicate that the knowledge variable has a significant positive effect on people's interest in saving at Bank Syariah Indonesia in Jambi City, the promotion variable does not affect people's interest in saving at Bank Syariah Indonesia in Jambi City and the location variable has a significant positive effect on people's interest in saving at Bank Syariah Indonesia in Jambi City.